Pemberdayaan Kader Kesehatan melalui Pemanfaataan Teknologi dengan Pemberian Edukasi Hipertensi dalam Meningkatkan Kesadaran dan Pencegahan Masyarakat Di Kelurahan Alalak Utara - Saftia Aryzki; Rina Saputri; Hairiana Kusvitasari; Jelita Annisa Putri; Nurul Zafirah; Monica Wikklin; Jesika Natalia; Emelia Haryanti Putri; Belva Handira (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Hypertension is a disease that is widely suffered by the community. Increasing public awareness of the importance of preventing hypertension is very necessary, especially at the community level. One way to increase awareness and prevention and control of the health of hypertension sufferers is to maximize the role of health cadres such as Posyandu cadres. Posyandu cadres have an important role as health educators in the village. Posyandu cadres must have sufficient knowledge and skills to be able to provide good and correct information according to their abilities. This community service activity aims to increase the knowledge and understanding of posyandu cadres regarding hypertension through educational media in the form of booklets, leaflets, digital-based posyandu health tools and health literacy books so that effective communication skills are created in providing education about hypertension. The method used in this community service is providing health education through counseling, mentoring and training of cadres, training in checking blood pressure, implementing pretests and posttests, and group discussions. The results of this activity are an increase in knowledge from posyandu cadres about hypertension. This can be seen from the results of the pre-test and post-test which showed an increase in knowledge of 8 cadres (80%) with an average pre-test and post-test score of 69 and 79. The increase in public knowledge and awareness of hypertension after receiving health education through technology has proven effective in strengthening the role of cadres in providing health services to the community, especially hypertension.